PENDIDIKAN KESEHATAN TENTANG SADARI PADA REMAJA - Marcellina Rasemi Widayanti; Irine Yunila Prastyawati (Jurnal Pengabdian Masyarakat, 2022)
Reproductive health in adolescent girls needs special attention, especially regarding breast self-examination/BSE as an early detection of breast cancer. The problem is the lack of knowledge of BSE in young women in the Palem Nirwana Sidoarjo Youth Association, the data is based on the results of interviews with 8 young women. The result: 5 people do not know BSE, 3 people have heard of it on TV but don't do it because they don't know how, someone tells that her friend had a lump on her breast and left it alone because there were no complaints, so she didn't check her breasts for lumps. Adolescents in the Palem Nirwana Sidoarjo Youth Association have never received health education about breast self-examination. apply to himself and can share this knowledge with his friends who do not know. After the Health education was carried out, the results of the evaluation of the majority of participants increased their knowledge. Furthermore, assistance is provided for the implementation of BSE. In conclusion, young women in the Paguyuban Palem Nirwana Sidoarjo are able to apply BSE without experiencing difficulties.